Job stress among community pharmacist in Klang Valley / Ahmad Najib Ahmad Afandi - Ahmad Afandi, Ahmad Najib (2009)
The total number of pharmacist in 2006 was 4292 pharmacists, and the ratio of pharmacists to the population in 2006 was I :6207. Despite the increasing number of pharmacists in Malaysia and the ratio of pharmacist to population is becoming narrower, the ratio in 2006 still suggest that Malaysia is still in the scenario of the shortage of pharmacists. This may cause a heavy workload for a single pharmacist, and thus leading to job stress. So, this research intends to identify the prevalence of job stress among pharmacists in Klang Valley, and what are the causes of the stress. The study will be conducted using the modified Hospital Consultants' Job Stress & Satisfaction Questionnaire 2002 developed by Cancer Research UK London Psychosocial Group. Respondents will be asked to rate each source of stress according to how much of a source of stress it was in their work on a 4-point scale of O (not at all), I (a little), 2 (quite a bit), 3 (a lot). The number of completed questionnaire returned was I 05 (29.25% response rate). Total overall score for each job stress inventory is calculated and ranked from the highest score to the lowest. It was found that the top three sources of job stress among community pharmacists in Klang Valley were "having too great an overall volume of work" , "having inadequate staff to do your job properly", and "dealing with patients or relatives having expectations of care that cannot be met". An additional of three job stressors were identified, they were "keeping up to date with current clinical and research practices", "having to comply with increasing bureaucratic and regulatory procedures", and "disruption of your home life through spending long hours at work". Further research is necessary to investigate deeper into the causes of job stress and impact of stress on pharmacists' life. Methods of solutions to reduce or control job stress are also necessary to make this area of research significant in the future. In addition, it is also important to see whether job stress among pharmacist is well managed or not.